Transition, text and turbulence: factors influencing children’s voluntary reading in their progress from primary to secondary school - Bouwer, A.C., 1946- (University of Pretoria, 2013)
Thesis (PhD (Learning Support, Guidance and Counselling))--University of Pretoria, 2006.